Ecotopians as Ecological Citizens: A Sustainable Ecological Life in Ecotopia: A Sustainable Ecological Life in Ecotopia - Sharma, Kamal (Tribhuvan University Journal, 2025)
Preservation of the natural resources to maintain ecological balance known as sustainability is based on green politics that valorizes each ecological being irrespective of speciesism, and nationalism. Growing concern of scholars about the depletion of natural resources and ecological degradation shows approaching environmental apocalypse. In this regard, this paper examines how a just sustainable society following green politics is at the heart of the newly formed country Ecotopia in the novel Ecotopia written by Ernest Callenbach. The novel is named after the fictional country Ecotopia which is formed through its secession from America. The country is ecologically intact and its practices look awkward to the most developed nations. The protagonist of the novel, William Weston, the top international affairs reporter, goes to Ecotopia for diplomatic relations. However, he decides to stay in Ecotopia forever even ignoring his family and nation. What attracts him to stay in this country by ignoring his family and country is a questionable issue. Here, I argue that his decision to stay as ecological being is his infatuation to the sustainable development and green politics which lie at the heart of Ecotopia as it firmly asserts the dissolution of hierarchy in its daily affairs including national and international politics. As a qualitative research, the paper follows the theoretical insight envisioned by Val Plumwood and Karen Warren who argue that hierarchy is a cause of downfall of equilibrium between nature and humanity. The research method involved in the study is textual analysis. The paper concludes that a hierarchy-less society is a foundation for sustainable ecological development. Weston’s decision to live in Ecotopia is the result of eco-centric practice. Thus, the paper serves a refreshing approach in the development model based on ecological balance.